A video‐based gait disturbance assessment tool for diagnosing idiopathic normal pressure hydrocephalus. Issue 3 (3rd December 2019) - Liao, Ruochen; Makihara, Yasushi; Muramatsu, Daigo; Mitsugami, Ikuhisa; Yagi, Yasushi; Yoshiyama, Kenji; Kazui, Hiroaki; Takeda, Masatoshi
Abstract: Gait is an important factor in the diagnosis of idiopathic normal pressure hydrocephalus. However, except for walking speed tests, existing diagnosis methods only assess gait qualitatively. This study proposes a quantitative and multifaceted method to assess gait disturbance via video‐based analysis. We captured videos of patients walking from the front to assess four gait disturbance qualities: lateral sway, petit‐pas gait, wide‐base gait, and duck‐footed walking. These features were selected from the Gait Status Scale‐Revised, an existing scale of idiopathic normal pressure hydrocephalus gait disturbance. We confirmed that our assessments of all selected items, except for lateral sway, were consistent with physician assessment. We also used the P ‐value of the gait disturbance scores before and after lumbar puncture to assess the outcome of the cerebrospinal fluid tap test, and confirmed that tap‐positive and tap‐negative patients were successfully separated by a threshold of P  = 0.01. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.